Epac: A Promising Therapeutic Target for Vascular Diseases: A Review - Yunfeng Pan; Yunfeng Pan; Yunfeng Pan; Jia Liu; Jiahui Ren; Jiahui Ren; Jiahui Ren; Yun Luo; Yun Luo; Yun Luo; Xiaobo Sun; Xiaobo Sun; et al. (Frontiers Media S.A., 2022)
Vascular diseases affect the circulatory system and comprise most human diseases. They cause severe symptoms and affect the quality of life of patients. Recently, since their identification, exchange proteins directly activated by cAMP (Epac) have attracted increasing scientific interest, because of their role in cyclic adenosine monophosphate (cAMP) signaling, a well-known signal transduction pathway. The role of Epac in cardiovascular disease and cancer is extensively studied, whereas their role in kidney disease has not been comprehensively explored yet. In this study, we aimed to review recent studies on the regulatory effects of Epac on various vascular diseases, such as cardiovascular disease, cerebrovascular disease, and cancer. Accumulating evidence has shown that both Epac1 and Epac2 play important roles in vascular diseases under both physiological and pathological conditions. Additionally, there has been an increasing focus on Epac pharmacological modulators. Therefore, we speculated that Epac could serve as a novel therapeutic target for the treatment of vascular diseases.